PENGEMBANGAN SISTEM INFORMASI AKUNTANSI RUMAH SAKIT (Studi Kasus: PKU Muhammadiyah Gombong) - Oman Rusmana; Eko Suyono; Warsidi * (Jurnal Pengabdian Bisnis dan Akuntansi Soedirman (JPBA), 2022)
The Objective of this community service was to identify the stages of implementation of accounting information systems and the factors that influence it. The study also aims to design an accounting system that consists of accounting documents, business processes, accounting policies, chart of accounts, account description, financial statement formats and standard journal entries. This research is a qualitative study using triangulation method of data analysis techniques, data sources and theory by the method of observation, interviews and distributing questionnaires. These results indicate that changes in the system is driven by the needs of stakeholders on the financial statements that can be responsibled for. The factors that most influence the success of the system is the individual factors. In the case, individuals who have very limited knowledge of accounting information systems inhibit the acceleration of change in accounting. The study also produced the original design, business processes, accounting policies in accordance with SAK ETAP, the format of financial statements, standard chart of accounts and journal entries.